Synergistic effects of free radical scavengers and cochlear vasodilators: a new otoprotective strategy for age-related hearing loss - Alvarado, Juan Carlos; Fuentes-Santamaría, Verónica; Melgar-Rojas, Pedro; Valero, María Llanos; Gabaldón-Ull, María Cruz; Miller, Josef M.; Juiz, José M. (Frontiers in Aging Neuroscience, 2015)
The growing increase in age-related hearing loss (ARHL), with its dramatic reduction in quality of life and significant increase in health care costs, is a catalyst to develop new therapeutic strategies to prevent or reduce this aging-associated condition. In this regard, there is extensive evidence that excessive free radical formation along with diminished cochlear blood flow are essential factors involved in mechanisms of other stress-related hearing loss, such as that associated with noise or ototoxic drug exposure. The emerging view is that both play key roles in ARHL pathogenesis. Therapeutic targeting of excessive free radical formation and cochlear blood flow regulation may be a useful strategy to prevent onset of ARHL. Supporting this idea, micronutrient-based therapies, in particular those combining antioxidants and vasodilators like magnesium (Mg2+), have proven effective in reducing the impact of noise and ototoxic drugs in the inner ear, therefore improving auditory function. In this review, the synergistic effects of combinations of antioxidant free radicals scavengers and cochlear vasodilators will be discussed as a feasible therapeutic approach for the treatment of ARHL.